Pengaruh Pembebanan Terhadap Efisiensi Transformator Distribusi Di PT. PLN (Persero) UP3 Garut - M. Reza Hidayat; Iqbal Fadilah (Sutet, 2023)
Transformer efficiency is defined as the ratio of the incoming power to the outgoing electric power. Even so the ideal transformer has 100% efficiency, this ideal transformer does not exist, because the energy that goes out is always less than the energy that goes in, meaning that there is energy loss. Load imbalance in an electric power distribution system always occurs and the imbalance is in single-phase loads in low-voltage network subscribers. Due to the load imbalance, a current appears in the neutral of the transformer. Perform analysis and compare efficiency. Analysis of used load capacity is not efficient. Analysis of the results of current and voltage measurements at the substation to obtain efficiency, and transformer losses in day and night conditions using LWBP and WBP methods. In this study, observations were made regarding the transformer efficiency analysis using the Outside Peak Load Time (LWBP) and Peak Load Time (WBP) methods. The LWBP method is carried out during the day for 20 hours, while the WBP method is carried out at night for 4 hours, from 18.00 to 22.00. Then measurements were made at PT. PLN (Persero) UP3 Garut. For the highest percentage of loading which is close to the standard of 80%, namely the afternoon loading at the PDDK substation, which is 50.93%, the load used is 50.93 kVA. The night load at the CITL substation is 77.49%, the load used is 77.49 kVA. For the lowest percentage of loading that deviates from the standard 80%, namely the daytime loading at the SJRK substation, which is 16.32%, the load used is 16.32 kVA. The night load at the SJRK substation is 21.52%, the load used is 21.52 kVA. Based on observations, it is not efficient because the unused load is very large, it is recommended to use a smaller transformer capacity. The highest efficiency in the LWBP method is at the CITK substation 97.87%, the lowest at the PDDK substation 94.55%. The highest efficiency in the WBP method is at SJRK substations 95.5%, the lowest at PDDK substations is 92.1%.